Comparison of medical comorbidities in Medicare patients treated by orthopaedic surgeons and neurosurgeons throughout the USA. (12th June 2020) - Beschloss, Alexander; Mueller, John; Caldwell, Jon-Michael E; Ha, Alex; Lombardi, Joseph M; Ozturk, Ali; Lehman, Ronald; Saifi, Comron
Abstract : Aims: Medical comorbidities are a critical factor in the decision-making process for operative management and risk-stratification. The Hierarchical Condition Categories (HCC) risk adjustment model is a powerful measure of illness severity for patients treated by surgeons. The HCC is utilized by Medicare to predict medical expenditure risk and to reimburse physicians accordingly. HCC weighs comorbidities differently to calculate risk. This study determines the prevalence of medical comorbidities and the average HCC score in Medicare patients being evaluated by neurosurgeons and orthopaedic surgeon, as well as a subset of academic spine surgeons within both specialities, in the USA. Methods: The Medicare Provider Utilization and Payment Database, which is based on data from the Centers for Medicare and Medicaid Services' National Claims History Standard Analytic Files, was analyzed for this study. Every surgeon who submitted a valid Medicare Part B non-institutional claim during the 2013 calendar year was included in this study. This database was queried for medical comorbidities and HCC scores of each patient who had, at minimum, a single office visit with a surgeon. This data included 21, 204 orthopaedic surgeons and 4, 372 neurosurgeons across 54 states/territories in the USA. Results: Orthopaedic surgeons evaluated patients with a mean HCC of 1.21, while neurosurgeons evaluated patients with a mean HCC of 1.34 (p < 0.05). The rates of specific comorbidities in patients seen by orthopaedic surgeons/neurosurgeons is as follows: Ischemic heart disease (35%/39%), diabetes (31%/33%), depression (23%/31%), chronic kidney disease (19%/23%), and heart failure (17%/19%). Conclusion: Nationally, comorbidity rate and HCC value for these Medicare patients are higher than national averages for the US population, with ischemic heart disease being six-times higher, diabetes two-times higher, depression three- to four-times higher, chronic kidney disease three-times higher, and heart failure nine-times higher among patients evaluated by orthopaedic surgeons and neurosurgeons. Cite this article: Bone Joint Open 2020;1-6:257–260.